ANALISIS YURIDIS PUTUSAN PAILIT TERHADAP PT.TELKOMSEL TBK - Ramli Siregar; Windha Windha (Universitas Sumatera Utara, 2014)
At this time the problems of bankruptcy, especially regarding the bankruptcy of a company in this case is a company-owned enterprises in the form of a limited liability company (PT) gets the spotlight and public attention from legal experts, non-governmental organizations as well as from law enforcement officers. Assessment of the public if a large state-owned enterprises company stated bankrupt raises a question as to why and how a company could be declared bankrupt, but is a great company. The problem in this writing is about an award to be insolvent if viewed review of Act No. 37 of 2004 regarding bankruptcy and suspension of debt payment obligation the authority of the commercial court is in check and prosecute a case of bankruptcy, as well as concerning the application of the provisions of the law on bankruptcy and pkpu in the case of the award bankruptcy PT.Telkomsel Tbk. Research methods used to draw up this thesis by the normative legal research or referred also to the study of librarianship (library research). Data collection is carried out by the research based on primary and secondary legal materials. Data collection tools from books, articles, magazines and the internet, which is closely related to the intent and purpose of this thesis writing. The conclusion of writing is that of a fallacy in this sense the award bankrupt based on law on bankruptcy and PKPU if not understood in more clear, and differences between the supreme court verdict on the commercial court until could have an award bankrupt occurs not because of debt but because the fastest defaults authority of a court in a cause especially in matters of the award bankrupt sometimes done without any a autonomy or irrespective of both parties equally until sometimes inflict a uncertainty law.